2020
DOI: 10.1007/s11214-020-00665-y
|View full text |Cite
|
Sign up to set email alerts
|

Physical Processes of Meso-Scale, Dynamic Auroral Forms

Abstract: Meso-scale auroral forms, such as poleward boundary intensifications, streamers, omega bands, beads and giant undulations, are manifestations of dynamic processes in the magnetosphere driven, to a large part, by plasma instabilities in the magnetotail. New observations from ground-and space-based instrumentation and theoretical treatments are giving us a clearer view of some of the physical processes behind these auroral forms. However, questions remain as to how some of these observations should be interprete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 191 publications
5
46
0
Order By: Relevance
“…Many of these auroral forms at Jupiter resemble mesoscale (Forsyth et al, 2020) and large-scale auroral forms observed during substorms at Earth. Furthermore, we found cases of consecutive dawn storms occurring within a few hours, similar to the nonisolated substorms at Earth.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Many of these auroral forms at Jupiter resemble mesoscale (Forsyth et al, 2020) and large-scale auroral forms observed during substorms at Earth. Furthermore, we found cases of consecutive dawn storms occurring within a few hours, similar to the nonisolated substorms at Earth.…”
Section: Discussionmentioning
confidence: 88%
“…Substorms are global reconfigurations of the magnetosphere during which the magnetic energy stored in the magnetotail is converted into particle energy, which lead to spectacular auroral brightening in nightside polar regions which generally follow a well‐established sequence of features (Akasofu, 2013). The transient spots observed in Jupiter's aurora share several morphological and temporal characteristics with transient mesoscale features on Earth, sometimes associated with poleward boundary intensifications and sometimes with streamers (Forsyth et al., 2020). Both are often observed before the substorm onset (Nishimura et al., 2011), even if the exact relationship between streamers and substorms is disputed (Miyashita & Ieda, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Within the aurora, meso‐scale (with scale sizes of 10–100s of kilometers) to small‐scale (with spatial scales down to tens of meters and temporal scales down to fractions of a second) structures appear as arcs, spots, patches, etc. of visual emissions with different luminosities and behaviors, most of which represent complex energy transport between magnetosphere and ionosphere (Borovsky et al., 1991; Frey, 2007; Forsyth et al., 2020; Maggs & Davis, 1968; Nishimura et al., 2020; Paschmann et al., 2012; Sandahl et al., 2008, etc.). The energy flow and structure within the auroral oval are therefore complicated and dynamic under different geomagnetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Still, all the above hypotheses have some drawbacks. Forsyth et al (2020) argues that the occurrence of a shear flow at the boundary between Region 1 and Region 2 currents, where the omega structures were recently mapped to (Liu et al, 2018), does not appear to be sufficient to generate an omega band, and that the region is generally stable to the shear flow instability. The BBF-associated mechanism allows one to explain the 3D current system associated with an individual omega structure (Amm, 1996;Amm et al, 2005;Opgenoorth et al, 1983), since BBFs have a similar pair of upward and downward field-aligned currents.…”
mentioning
confidence: 99%